SOSIALISASI NORMA-NORMA HUKUM TENTANG KEWAJIBAN PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY BAGI PERUSAHAAN YANG BERGERAK DI BIDANG KEPARIWISATAAN DI SANUR - N K. Supa sti Dharmawan; A. A. Sri Indrawati; D. G. Rudy; N P. Purwanti; W. Wiryawan; I. B. P. Sutama (Buletin Udayana Mengabdi, 2013)
Originally the concept of CSR in developed countries is voluntary (voluntary based). Otherwise, in IndonesiaCSR is developed on the basis of legal obligation (mandatory based). Legal norms which expressly stipulatelegal obligation for the company to implement Corporate Social Responsibility (CSR) is the Law 40 /2007 onLimited Liability Companies, Government Decree No. 47/ 2012 and Act No. 25/2007 on Investment. Accordingto the Article 74 of Law No. 40/ 2007 as well as the Article 3 Government Decree No. 47/2012, each companyrunning its business activities in the field and / or related to the natural resources is required to carry out socialand environmental responsibility including companies engagement in the field of tourism in Sanur Bali. VariousCSR activities for the tourism companies in Sanur Bali, besides referring to the legislation are also expected torefer to the concept of Triple Bottom Line (Profit, People, Planet). These are designed to make balance betweenprofit related to People and the Planet for CSR perspective, as well as ISO 26000.